Problems And Solutions In Training Engineering Personnel - Abdurakhmanov Abdurashid Atakhanovich (Genius Journals, 2026)
This article analyzes the main problems arising in the process of training engineering personnel in Uzbekistan and proposes practical recommendations for their solution. Within the framework of cooperation between researchers, educational institutions, and industrial enterprises, the quality of education and the factors influencing it are examined. The issues of improving educational effectiveness through modernization of the education system, updating methodological resources, and implementing modern technologies are considered
Keywords: engineering; education system; education